10-26-92 - Charles Weyant - Librarian LBCC - Linn-Benton Community College; L. Wallace (1992)
Image 34 was used in Volume 24, Edition 4: http://libarchive.linnbenton.edu/concern/newspaper_issues/vt150j31m?locale=en